Understanding Marriage Determinants on Working Age: ปัจจัยที่กำหนดการสมรสในวัยทำงาน - Potchanasit, Pratumma; Hong-Ngam, Jongrak; Srungboonmee, Tanyamat (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ การศึกษาครั้งนี้ดำเนินการภายใต้วัตถุประสงค์เพื่อศึกษาปัจจัยที่ส่งผลต่อการสมรสของวัยทำงานเพื่อสังเคราะห์แนวทางให้แก่หน่วยงานที่เกี่ยวข้องในการส่งเสริมและวางแผนการเปลี่ยนแปลงของตลาดแรงงานในอนาคต พร้อมทั้งกำหนดแนวทางส่งเสริมการสมรสและมีบุตรเพื่อแบ่งเบาภาระการอุ้มชูผู้สูงวัยในอนาคต ในการศึกษาผู้วิจัยได้เก็บตัวอย่างจากวัยทำงานในจังหวัดหนองบัวลำภูทั้งสิ้น 349 คน ด้วยวิธีการสุ่มแบบอย่างง่าย และทำการวิเคราะห์ข้อมูลพื้นฐานด้วยหลักสถิติเชิงพรรณนา พร้อมทั้งหาปัจจัยที่ส่งผลต่อการสมรสด้วยแบบจำลองถดถอยโพรบิท ผลการศึกษาในครั้งนี้ปรากฏว่า ปัจจัยทางด้านการศึกษา เจเนอเรชัน จำนวนพี่น้องในครอบครัว และบุคลิกภาพพื้นฐานของตัวบุคคล ส่งผลต่อการสมรสอย่างมีนัยสำคัญทางสถิติ ABSTRACT This paper was undertaken to explore marriage determinants among the working-age population in order to examine appropriate policy recommendations for relevant authorities to deal with changing labor market in the future. This study was conducted with survey data with 349 individuals we also use the simple sampling method in the collecting data process. To analyze data, descriptive statistics were used to summarize the characteristics of the sample and used the inferential statistic as a probit regression model to indicate the factors influencing the marriage. The empirical results reveal that the “education levels” “generation” “number of siblings” and “personal behavior” affecting marriage for the working-age population with statistically significance.